Impact of sepses caused by three Multi-Drug Resistant bacteria in a tertiary hospital in 2018-2020: Jacopo Garlasco. (25th October 2022) - Garlasco, J; Beqiraj, I; Bolla, C; Marino, EMI; Zanelli, C; Rocchetti, A; Gianino, MM
Abstract: Background: Healthcare-associated infections represent a major health issue, particularly if caused by multi-drug resistant (MDR) microorganisms, with additional hospitalisation days and relevant costs besides illness and deaths. This study aimed at evaluating the economic impact of healthcare-related sepses caused by three MDR Gram-negative bacteria (Acinetobacter baumannii, Klebsiella pneumoniae and Pseudomonas aeruginosa) in a tertiary hospital. Methods: An observational, retrospective-cohort analysis was based on data related to patients admitted to the "SS. Antonio e Biagio e Cesare Arrigo" Hospital in Alessandria (Italy) between 2018 and 2020. Starting from the microbiology laboratory database, the set of patients developing sepses from the examined species was selected, by also checking that the relevant antibiogram provided evidence of resistance to ≥ 2 antimicrobial classes indicated by the European Centre for Disease Prevention and Control. Data were retrieved from patients' medical records and from the hospital's computer-based application. Results: In years 2018-2020, 174 patients developed septic infections from the examined species, the majority of which (88, i.e. 50.6%) in 2020 only. Altogether, these cases were responsible for 3, 295 additional hospitalisation days (median 14 days, mean 19 days), with 901 imaging and 7, 365 laboratory exams being reasonably ascribable to the septic episodes. Sepsis-related costs could be estimated in around 3 million Euros, about 85% of which (≈2.5 million Euros) were due to the actual cost of extra hospital stay. Specific antimicrobial therapy accounted for around 11.2% of the total (≈336, 000 €). Conclusions: The results of this study pointed out that MDR sepses were responsible for conspicuous costs, largely grounded on the extra length of hospital stays but also due to the use of highly-expensive new-generation antimicrobials. Further research is needed to explore costs of septic episodes in different contexts. Key messages: MDR sepses entailed high costs (around 3 million Euros in three years only in a single hospital), due to extra length of hospital stays and use of highly-expensive new-generation antimicrobials. In order to provide wider-scale estimates of the economic impact of sepses, further research is needed to explore costs of septic episodes in different sanitary systems and contexts.